2013
DOI: 10.1021/nn402354j
|View full text |Cite
|
Sign up to set email alerts
|

Focused-Laser-Enabled p–n Junctions in Graphene Field-Effect Transistors

Abstract: With its electrical carrier type as well as carrier densities highly sensitive to light, graphene is potentially an ideal candidate for many optoelectronic applications. Beyond the direct light-graphene interactions, indirect effects arising from induced charge traps underneath the photoactive graphene arising from light-substrate interactions must be better understood and harnessed. Here, we study the local doping effect in graphene using focused-laser irradiation, which governs the trapping and ejecting beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
105
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(118 citation statements)
references
References 51 publications
13
105
0
Order By: Relevance
“…On the other hand, laser irradiation of graphene on silicon oxide leads to a horizontal shift, consistent with an increase in hole doping as well as in compressive strain, in agreement with recent experiments performed by laser pulses. 9,10 This interpretation is also supported by the behaviour of the linewidth of the G peak, presented in Fig. 3(b), where a substrate-dependent response was observed.…”
Section: Dsupporting
confidence: 69%
See 2 more Smart Citations
“…On the other hand, laser irradiation of graphene on silicon oxide leads to a horizontal shift, consistent with an increase in hole doping as well as in compressive strain, in agreement with recent experiments performed by laser pulses. 9,10 This interpretation is also supported by the behaviour of the linewidth of the G peak, presented in Fig. 3(b), where a substrate-dependent response was observed.…”
Section: Dsupporting
confidence: 69%
“…5,6 One of the most attractive characteristics of graphene is the ability to control its electronic and optical properties through the charge carrier density. This can be achieved by chemical, 7 electronic, 1 optical, [8][9][10] or mechanical 11 means. Moreover, it has been suggested that the electronic and optical properties of graphene depend strongly on its strain distribution.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the thermal radiation from electrically biased graphene supported on a substrate 8,9,[15][16][17] has been found to be limited to the infrared range and 3 to be inefficient as an extremely small fraction of the applied energy (~ 10 -6 ) 8,9 is converted into light radiation. Such limitations are the direct result of heat dissipation through the underlying substrate 18 and significant hot electron relaxation from dominant extrinsic scattering effects such as charged impurities 19 and surface polar optical phonon interaction 20 , limiting the maximum operating temperatures.On the other hand, a freely suspended graphene is mostly immune to such undesirable vertical heat dissipation 10 and extrinsic scattering effects 21,22 , promising much more efficient and brighter radiation in the infrared-to-visible range. Fortuitously, due to the strong Umklapp phonon-phonon scattering 23 , we find that the thermal conductivity of graphene at high lattice temperatures (1800 ± 300 K) is greatly reduced (~ 65 Wm -1 K -1 ), which additionally suppresses lateral heat dissipation; therefore, hot electrons (~ 2800 K) become spatially localised at the centre of the suspended graphene under modest electric fields (~ 0.4 V/µm), greatly increasing the efficiency and brightness of the light emission.…”
mentioning
confidence: 99%
“…It possesses exceptional thermal, electrical, optical and mechanical properties leading to its potential applications in research and industry as transparent electrodes, field emitters, biosensors, etc. [1][2][3][4][5][6][7][8]. Graphene has been prepared by several techniques viz.…”
Section: Introductionmentioning
confidence: 99%